Thermographic analysis of the lower limbs before and after application of the whole body vibration technique: Comparative study (Research, Society and Development, 2025)
Introduction: Whole-body vibration can cause changes in peripheral blood perfusion, making infrared thermography an essential tool for analyzing the thermographic adaptations generated. Objective: to evaluate the thermographic repercussions in the anterior and posterior regions of the thigh and leg, comparing the oscillation and vibration modes of a whole-body vibrating platform in healthy individuals. Materials and methods: This comparative, descriptive, and quantitative study, approved by the Research Ethics Committee of the University of Ribeirão Preto (CAAE 74029023.4.0000.5498), selected four sedentary women, with a mean age of 21.5 ± 0.5 years. The participants underwent seven 10-minute sessions in oscillation mode and seven in vibration mode, with infrared thermography (FLIR C3x camera) performed before and after each session in a controlled room.  Data analysis was performed statistically using SPSS Statistics v.25, using independent and paired t-test with p